DINAMIKA BENTUK KENAKALAN REMAJA DI DESA MONCONGLOE LAPPARA KECAMATAN MONCONGLOE KABUPATEN MAROS - Haeruddin; Andi Haris; Rahmat Muhammad (Halu Oleo University, 2025)
Juvenile delinquency in the community of Moncongloe Lappara Village, Moncongloe District, Maros Regency is a complex and multidimensional issue, indicating a significant weakening of informal social control at the family and community levels. This study used a qualitative approach to deeply explore various forms of juvenile delinquency in Moncongloe Lappara Village, Maros Regency. Through in-depth interviews with key informants from the village community, data were collected to understand the complexity of this phenomenon from a subjective perspective, as well as through field observations and related document analysis. The findings from the research indicate that juvenile delinquency in Moncongloe Lappara Village is not only diverse but also shows a significant weakening of informal social control, particularly in the role of the family and community.